Chronic unexplained nausea in adults: Prevalence, impact on quality of life, and underlying organic diseases in a cohort of 5096 subjects comprehensively investigated. - Hye-Kyung Jung; Chung Hyun Tae; Chang Mo Moon; Seong-Eun Kim; Ki-Nam Shim; Sung-Ae Jung (PLoS ONE)
We evaluated to define the clinically significant chronic nausea in general population and to assess the prevalence of chronic unexplained nausea after exclusion of organic causes through the meticulous medical examination. Two phase studies were conducted. In phase 1, telephone survey was conducted to define the clinically significant nausea in 5000 representative subjects for a general population. Clinically significant nausea was identified by lowered quality of life if the frequency was 'more than one day per week'. Its prevalence was 1.6% (1.4-1.8%) and about 90% of nausea was not accompanied with vomiting. In phase 2, 5096 participants in a comprehensive health-screening cohort were enrolled. We investigated demographics, gastrointestinal symptoms, somatization symptoms and health related quality of life using validated questionnaire. All participants underwent meticulous medical examinations including endoscopy, abdominal ultrasound, thyroid function test, and blood testing. Among a total of 5096 subjects (men 51.8%, mean age 47.5 ± 10.0 years), organic diseases associated with chronic nausea were reflux esophagitis, duodenal ulcer and hyperthyroidism. The prevalence of chronic unexplained nausea was 0.6% (95% CI 0.4-0.8%) and there were significant overlap with functional dyspepsia and irritable bowel syndrome. HRQoL is significantly lower in people with nausea occurring 'more than one day per week' in a general population. Most chronic nausea was not accompanied with vomiting. Chronic unexplained nausea is uncommon affecting only 0.6% of the population but are more likely to report functional dyspepsia and irritable bowel syndrome.